Efficacy and safety of Lacticaseibacillus rhamnosus R0011 and Lactobacillus helveticus R0052 as an adjuvant for Helicobacter pylori eradication: a double-blind, randomized, placebo-controlled study - Kiattiweerasak, Anya; Aumpan, Natsuda; Chonprasertsuk, Soonthorn; Pornthisarn, Bubpha; Siramolpiwat, Sith; Bhanthumkomol, Patommatat; Nunanan, Pongjarat; Issariyakulkarn, Navapan; Mahachai, Varocha; Yamaoka, Yoshio; Vilaichone, Ratha-korn (Frontiers in Gastroenterology, 2023)
BACKGROUND: H. pylori eradication is recommended to provide symptomatic relief for dyspepsia.Limited efficacy of triple therapy is a major problem in many countries, including Thailand. Some probiotics were shown to improve H. pylori eradication rate and reduce side effects. This study aimed at evaluating the efficacy of probiotic (Lacidofil® STRONG) as adjuvant to standard triple therapy.This randomized, double-blind, placebo-controlled study was conducted between July 2020 and June 2022. Eligible patients with H. pylori gastritis (N=90/160 screened) were randomized to receive 14-day standard triple therapy with probiotic or with placebo (N=45/group). Treatment regimen comprised 30 mg lansoprazole twice daily, 1000 mg amoxicillin twice daily, and 1 gram clarithromycin modified-release formulation once daily. A probiotic capsule containing Lacticaseibacillus rhamnosus R0011 and Lactobacillus helveticus R0052 (Lacidofil® STRONG) or placebo were given twice daily during the eradication therapy and for additional 4 weeks. Successful H. pylori eradication was defined as negative 13 C-urea breath test at least 4 weeks after complete eradication.As per-protocol analysis, eradication rates of 14-day regimen with probiotic or placebo were 90.9% and 75.0% (p=0.047), respectively. Antibiotic susceptibility testing demonstrated high clarithromycin resistance (24%). For clarithromycin-resistant strains, there was no statistical difference in eradication rates between the probiotic and placebo group. Furthermore, probiotic supplementation significantly reduced treatment side effects including bloating (OR 0.27[95%CI 0.10-0.75], p=0.012), diarrhea (OR 0.23[95%CI 0.28-0.65], p=0.006), nausea (OR 0.05[95%CI 0.01-0.36], p=0.003), and bitter taste (OR 0.14[95%CI 0.03-0.69], p=0.015). The probiotic group had lower Gastrointestinal Symptom Rating Scale (GSRS) score (1.46±0.36 vs. 2.65±0.66, p<0.001) and higher SF-36 healthrelated quality-of-life score (63.3±10.2 vs. 57.3±13.4, p=0.020) after treatment.The probiotic adjuvant with 14-day standard triple therapy improved H. pylori eradication rate. Supplementation with Lacidofil® STRONG during 2-week eradication treatment and 4-week follow-up phase can help reduce gastrointestinal side effects of eradication therapy and increase general health-related quality of life.